Phenomenon Endowment in Arabic - Dr. Adulwahb Ibrahim Elmhroog (Journal of Scientific and Human Dimensions, 2026)
An Phenomenon  l knew  her  Arabic  since  Its origin  And he knew  About  the  Arabs  They  They  don t start  Basakin  And they  do not stop  On a moving  That’s  Iightness  Stillness   And the endowment  Against  connection  Therefore  Waqf (endowment) has different  aspects  several  she: Stopping  with a pause, And the Romans, And with the nasalization  And by transport , By doubling,  And it has been shown  This phenomenon  Scholars  of Tajweed  And the voices,  And we showed its Iocations  So she adorned herself  with it   Arabic  And increased  its splendor, He participated  in detail  This phenomenon  Scintists  Grammar  And the exchange  And the voices  and   Tajweed.
Keywords: Tanween; Endowment; the Quran; Romans